Phenotypic Insights Into Beta-Lactamase-Mediated Multidrug Resistance In Escherichia Coli Clinical Isolates - Baral, Soma Kanta; Dhakal, Abinash; Timilsina, Rabindra Prasad; Manandhar, Krishna Das; Poudel, Pramod (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: The global rise of multidrug-resistant (MDR) bacteria is largely attributed to the production of β-lactamases, including extended-spectrum β-lactamases (ESBLs), metallo-β-lactamases (MBLs), and AmpC β-lactamases. This study aimed to evaluate the phenotypic characteristics of β-lactamase-producing MDR Escherichia coli isolates and assess their antibiotic resistance profiles. Method: A cross-sectional study was conducted over six months (November 2021–April 2022) at Manmohan Memorial Teaching Hospital, Kathmandu. Clinical samples were processed using standard microbiological techniques to isolate E. coli. The Kirby-Bauer disk diffusion method was used for antimicrobial susceptibility testing. Phenotypic detection of ESBL, MBL, and AmpC β-lactamases was performed using the combined disk method. Results: Out of 127 E. coli isolates, 55 (43.3%) were identified as MDR. Among these, 26 (47.3%) expressed β-lactamase activity: AmpC (34.54%), MBL (7.27%), and ESBL (5.45%). No co-existence of β-lactamases was observed. High resistance was noted against amoxicillin (100%), cefixime (90.9%), and cotrimoxazole (85.5%), whereas amikacin (90.9%) and meropenem (89.0%) showed strong effectiveness. Conclusion: AmpC β-lactamase was the predominant resistance mechanism among MDR E. coli isolates. Early detection of β-lactamase production is crucial for effective infection control and to curb the spread of MDR pathogens.